Сообщество ритуала модернизации: от логоса к культу - Кутуев, П. (Социология: теория, методы, маркетинг, 2007)
The essay traces the evolution of the discourse on modernity in classical sociological theory. Then it moves on to conceptualize the causes and consequences of abuse of modernization theory by some members of Ukrainian academic community who distort its background assumptions. The article argues that these persons have created a community of ritual, thus rejecting the rational norms underlying research activities in a modern society. This community treats modernization not as a concept elaborated within the framework of rational discourse but as a phenomenon akin to cargo cult. The article examines how members of the community of modernization cult construct pseudo-scientific illusion of their theory, methodology, sources and even subject-matter. It is suggested that the only antidote to this type of degenerative transformation of a logos into a cult is the revival of the culture of critical discourse in Ukrainian academic community.